Proof of concept : the effectiveness of disinfectant tunnel as potential measure against COVID-19 - Noratiqah Mohtar; Nur Hafzan Md. Hanafiah; Ng, Sui Yee; Amirah Mohd Gazzali; Thaigarajan Parumasivam (Penerbit Universiti Kebangsaan Malaysia, 2021)
Disinfectant tunnels have attracted attention as a potential measure to prevent the spread of COVID-19, but their safety and effectiveness are questionable. Disinfectants such as sodium hypochlorite were used, yet no scientific evidence is available on its effectiveness to eliminate SARS-CoV-2 on the human body through spraying, although this chemical is effective in the elimination of the virus on inanimate surfaces. Since safety issues are of importance, countries have halted the operation of these tunnels. Available literature has suggested several effective disinfectants against SARS-CoV-2, including iodine-based solution, such as povidone-iodine (PVP-I). This report describes the evaluation of the bactericidal activity of PVP-I in comparison to sodium hypochlorite, both in vitro and following spraying under a model tunnel. Two bacteria strains (Pseudomonas aeruginosa ATCC 27853 and Staphylococcus aureus ATCC 12600) were used as model microorganisms. The spraying pattern and droplets distribution from the tunnel are also being described and were correlated with the effectiveness of the disinfectant droplets to eliminate the model bacteria. Results showed that 0.5 % v/v PVP-I and 0.5% v/v sodium hypochlorite are bactericidal (> 5 log10 reduction) in vitro. However, sprayed disinfectants did not show similar activity. Bacterial growth was seen in all cloth samples for 0.5% v/v PVP-I and all cloth samples except right shoulder for 0.5 % v/v sodium hypochlorite. Hence, the design of any disinfectant tunnel is important, and with an effective disinfectant to justify its efficacy.